Podróże Zofii Stryjeńskiej i ich paryskie etapy - Lenartowicz, Światosław (Archiwum Emigracji, 2012)
The article is devoted to Zofia Stryjeńskas’ (1891–1976) travels abroad and her fates during emigration after World War II. The most important aim of her travels, as well as a safe haven during emigration was Paris. The author discusses the artists’ individual stays in Paris and characterizes her works connected with them.